EdTech Initiatives Focused on Classrooms and Teachers: A Curated List for Rwanda - Chuang, Rachel; Koomar, Saalim (EdTech Hub, 2020)
This document was produced in response to a request from the FCDO Rwanda team for a curated list of EdTech initiatives related to the following focus areas: 1. Classroom software 2. Teacher education 3. School administration.
ZenodoArchiveID: 4762316 previousDOI: 10.5281/zenodo.4050155 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4762316 10.5281/zenodo.3990369 10.5281/zenodo.4050155 10.5281/zenodo.4762316 10/ghgk62 2339240:86AAWUD3 2339240:BMRM6MNQ 2339240:RYU57YK3 2405685:BMDY65UF 2405685:CHX3W9RE 2405685:WGYWI78R
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted

Using EdTech to Support Effective Data Monitoring: A Curated Resource List. - Koomar, Saalim; Blest, Harriet (EdTech Hub, 2020)
This list curates resources on the use of EdTech to support the effective monitoring of educational outcomes, such as learning, reporting, and attendance. Resources shared are both tools and initiatives that can be adapted to support effective educational monitoring.
ZenodoArchiveID: 4762325 previousDOI: 10.5281/zenodo.4762325 PREV_DOI_NOT_ETH: 10.5281/zenodo.4091396 shortDOI: 10/ghgng6 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3407517 10.5281/zenodo.4762325 10/ghgng6 2339240:C9LP4Y2Z 2339240:EKNZDSVU 2339240:GMJF38V5 2339240:MZKWF23D 2339240:QJX4VXGR 2405685:7I4HVAV2 2405685:884LRL46 2405685:ANHT4I3J 2405685:FS4CMYUB 2405685:RV39YP9Q 2405685:WCYEVIJU 4656463:K7HMFX7H
Keywords: C:Mozambique; ES:Educational data; ES:Monitoring and evaluation; F: Helpdesk response; L:Low-level foundational skills; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted